RELATIONSHIP MARKETING AND BUSINESS STRATEGY OF PERÚ - Barrón Aráoz, Ricardo Ampelio (2011)
Currently, many companies in the world in the line of business are developing business models based on relationship marketing, it is explained that the transactional approach was increasingly unable to provide fully satisfactory answers to contemporary business problems. At the same time has created new technical possibilities, especially in the field of information technology and communications, which have opened new horizons to a new type of marketing: relationship marketing. Very few companies have the skills and strategies to retain or improve the profitability of existing customers, something that today is considered much more important. However, the relationship marketing or CRM remains a rather neglected by ordinary companies in Peru. No wonder that one of the most common problems in business is the lack of consistency among employees when interacting with customers. This article seeks to highlight the importance of developing a model for managing customer relationships based on relationship marketing, as well as assess the current position of Peruvian companies in the international economy based on the application of CRM.